Tuft cell cysteinyl leukotrienes are necessary for rhinovirus-induced mucus metaplasia, type 2 inflammation and airway hyperresponsiveness in immature mice - Parker, De’Jana T.; Bentley, J. Kelley; Lei, Jing; Domala, Baljeet; Briggs, Hannah L.; Singh, Shilpi; Li, Yiran; Reiner, M. Claire; Flores, Derek A.; Sliwicki, Alex L.; Flori, Heidi R.; Hershenson, Marc B. (Frontiers in Immunology, 2026)
IntroductionEarly-life wheezing-associated respiratory tract infections with rhinovirus (RV) are considered risk factors for asthma development. Cysteinyl leukotrienes (cysLTs) are pro-inflammatory lipid mediators synthesized from arachidonic acid by 5-lipoxygenase (Alox5) and Alox5 activating protein (Alox5ap). We hypothesized that tuft cell-derived cysLTs are required for the development of an asthma phenotype in immature mice undergoing heterotypic RV infection.MethodsWe infected C57BL/6, Alox5-/- or Pou2f3-/- mice lacking tuft cells with sham HeLa cell lysate or RV-A1B on day 6 of life and RV-A2 on day 13 of life. Selected mice were treated with montelukast or vehicle. Lungs were harvested on day 21 for ELISA, histology, immunohistochemistry, immunofluorescence microscopy and qPCR. Airways responsiveness to methacholine was determined by plethysmography. We also examined nasal swabs from children hospitalized with RV bronchiolitis for ALOX5 and ALOX5AP transcripts.ResultsAfter heterologous RV infection, C57BL/6 mice showed increased lung cysLT levels and mRNA expression of Alox5 and Alox5ap. ALOX5 and ALOX5AP were also increased in infants with RV bronchiolitis. RV-infected mice demonstrated rare Alox5+, Alox5ap+ and Dclk1+ cells in the airway epithelium, indicating the presence of tuft cells. RV-infected Pou2f3-/- mice showed reduced lung cysLT production and an absence of Alox5+, Alox5ap+ or Dclk1+ epithelial cells. Alox5-/- and Pou2f3-/- mice, as well as montelukast-treated C57Bl/6 mice, showed reduced Muc5ac levels, PAS staining, airways responsiveness and mRNA expression of Il4, Il5, Il13 and Il25.ConclusionsTuft cell-derived cysLTs are required for mucous metaplasia, type 2 inflammation and airways hyperresponsiveness in immature mice exposed to heterologous viral infection.